2017
DOI: 10.1111/bph.13956
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of cognition: a panacea for neuropsychiatric disease?

Abstract: Linked Articles This article is part of a themed section on Pharmacology of Cognition: a Panacea for Neuropsychiatric Disease? To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v174.19/issuetoc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…MMN is not only a cognitive biomarker but also a biomarker for negative symptoms in schizophrenia [147]. The pharmacology of cognition as a panacea for neuropsychiatric diseases was recently published [148]. This is important because neuropsychological tests were unable to distinguish CIAS versus cognitive impairments after traumatic brain injury [149].…”
Section: Mismatch Negativitymentioning
confidence: 99%
“…MMN is not only a cognitive biomarker but also a biomarker for negative symptoms in schizophrenia [147]. The pharmacology of cognition as a panacea for neuropsychiatric diseases was recently published [148]. This is important because neuropsychological tests were unable to distinguish CIAS versus cognitive impairments after traumatic brain injury [149].…”
Section: Mismatch Negativitymentioning
confidence: 99%
“…Nicotinic and NMDA receptors seem to be the underlying mechanism of major symptoms and biomarkers in many neuropsychiatric diseases (Koola, 2018c; Koola et al, 2019) as shown in Figure 3. The pharmacology (same combinations) of cognition may be a solution in the treatment of neuropsychiatric disorders (Bailey, Neill, & Moran, 2017). The strategy of targeting nicotinic‐cholinergic and glutamatergic/NMDA systems simultaneously (Table 2) may be a golden opportunity for novel therapeutic discovery.…”
Section: Schizophrenia and Beyondmentioning
confidence: 99%